The Brescia Smart Campus Demonstrator. Renovation toward a zero Energy Classroom Building. (2015) - De Angelis, E.; Ciribini, A.L.C.; Tagliabue, L.C.; Paneroni, M.
Abstract: The project is framed into the activities addressing the Smart Campus at University of Brescia. The classroom building is used as demonstrator of the energy strategies to improve the performance of existing buildings toward zero energy goals. Innovative systems to reduce energy consumption (i.e. heating, cooling and ventilation, lighting and electric equipment) and Smart Automation are crucial in the Smart Campus School Project of which this research is a preliminary step of development. The project is based on three main pillars: envelope refurbishment, improvement of building services efficiency, smart control of energy picking and placing peaks on the electrical net, also using energy uses other than building services (e.g. electrical vehicle charging station). The activities have been organized in phases, starting from the analysis of the possible interventions to improve the energy quality of the building and evaluating the efficiency of different measures. At the same time a plan for a preliminary operational conditions monitoring have been developed to increase the confidence and awareness on energy consumptions. The second phase is focused on consumption smart monitoring, users' behavior control and validation on technical and economic criteria. Moreover the demonstrator aims to define an interoperability practice, in order to enhance BIM to BEM procedures. In the paper, the preliminary phase of the research based the first pillar is described evaluating the energy reduction through envelope renovation and renewable energy production to pursue an energy balance between generation and consumption.